Project Performance And Delays In Sudan Construction Industry - Elhassan, Salma Abdalrahman Mohamed (2009)
The construction industry in Sudan is facing several problems and challenges such as poor performance of projects and delay in completion of construction projects. This research seeks to identify those factors that enhance performance of the projects, as well as the factors that lead to the delay of projects in Sudan. A substantial literature done to obtain the information on factors that influence project performance and factors that cause the construction delay from previous researchers, from which forty one factors were identified for project performance and ten factors that cause delay. A total of 70 designed structured questionnaires were distributed to construction firms in Khartoum and 52 questionnaires were completed and returned. The Relative Importance Index (RII) was used to rank the factors that influence project performance and causes of delay.